Residual LCMV antigen in transiently CD4+ T cell‐depleted mice induces high levels of virus‐specific antibodies but only limited B‐cell memory. Issue 4 (4th February 2019) - Schweier, Oliver; Aichele, Ulrike; Marx, Anna‐Friederike; Straub, Tobias; Verbeek, J. Sjef; Pinschewer, Daniel D.; Pircher, Hanspeter
Abstract: Infection of C57BL/6 mice with lymphocytic choriomeningitis virus (LCMV) strain Armstrong (Arm) induces an acute infection with rapid virus clearance by CD8 + T cells independently of CD4 + T cell help. Residual viral antigen may, however, persist for a prolonged time. Here, we demonstrate that mice that had been transiently depleted of CD4 + T cells during acute LCMV Arm infection generated high levels of virus‐specific IgG antibodies (Ab) after viral clearance. Robust induction of LCMV‐specific IgG after transient CD4 + T cell depletion was dependent on Fcγ receptors but not on the complement receptors CD21/CD35. In contrast to the potent production of LCMV‐specific IgG, the generation of LCMV‐specific isotype‐switched memory B cells after transient CD4 + T cell depletion was considerably reduced. Moreover, mice depleted of CD4 + T cells during acute infection were strongly impaired in generating a secondary LCMV‐specific B cell response upon LCMV rechallenge. In conclusion, our data indicate that LCMV antigen depots after viral clearance were capable of inducing high levels of virus‐specific IgG. They failed, however, to induce robust virus‐specific B cell memory revealing a previously unappreciated dichotomy of specific Ab production and memory cell formation after priming with residual antigen. Abstract : Mice transiently depleted of CD4 + T cells during acute LCMV infection generate a robust LCMV‐specific IgG response after viral clearance. In contrast, LCMV‐specific memory B cells (Bm ) are poorly induced. Hence, LCMV antigen depots are capable to trigger a strong virus‐specific antibody but not a memory B cell response.